Microstructure and low-cycle fatigue performance of selective electron beam melted Ti6Al4V alloy. (October 2022) - Zhang, Yinling; Fang, Xiaoying; Wang, Hongtao; Zong, Ran; Zhao, Ertuan; Han, Jinguo; Dong, Zhichao; Zhang, Zhixiong
Graphical abstract: Highlights: Relationship among microstructure, tensile properties and fatigue performance of SEBM-Ti6Al4V alloy was investigated. A non-theoretical α/α misorientation at an angle of 30° is detected in the β → α phase transformation. Cyclic stabilization retained despite cyclic softening at higher strain amplitudes for 45°-oriented specimens. A strain-energy density based model accurately predicted the fatigue life via a modified approach for the determination of intrinsic fatigue toughness. Abstract: Additive manufacturing is a key element in fueling the fourth Industrial Revolution. Selective electron beam melting is one of the promising additive manufacturing methods for titanium components. In this work, microstructure and mechanical properties of selective electron beam melted Ti6Al4V alloy were investigated. A non-theoretical α/α misorientation angle of 30°/[1 1 −2 0] is detected in the β → α phase transformation, which can aid in the act of deformation behavior during tensile testing. The horizontally built specimens exhibit a higher strain rate sensitivity of 0.005–0.017. While the highest strength occurs in selective electron beam melted 45°-oriented built tensile specimens due to texture effect of α variants. Cyclic stabilization mostly remained except mild cyclic softening happened above 0.6%. An energy density-based model integrated with the accumulative damage process is employed to predict fatigue life via a modified method for evaluating of intrinsic fatigue toughness, which is defined as the sum of all hysteresis loop areas from the first cycle to the last cycle. This method is expected to promote the practical application of selective electron beam melted Ti6Al4V material.